39. ASSESSMENT OF PSYCHOLOGICAL AND PHYSIOLOGICAL FUNCTION IN PATIENTS AFTER TOTAL HYSTERECTOMY DUE TO CANCER AT THE DEPARTMENT OF GYNECOLOGY AND SURGERY, K HOSPITAL IN 2023 (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate psychophysiological function in patients after total hysterectomy due to cancer at the Department of Gynecological Surgery, K Hospital in 2023.Subjects: Patients aged 18 to 55 years who have undergone a total hysterectomy.Method: Cross sectional study.Results: 106 patients after cervical cancer surgery were interviewed using a set of DASS 21 and FSFI questionnaires. The main age is from 30-55 years old (89.62%), having a high school degree or higher (87.73%), living with a husband (84.91%), most of whom have just had surgery once (93.4%).  There were 12.26% of patients with varying degrees of depression; 30.19% of patients showed varying levels of anxiety; 26.42% of patients showed signs of stress at different levels. 100% of patients had sexual physiological disorders, the average of total scale was 14.76 ±2.72; The scores for each area were pain (1.87/6), satisfaction (2.12/6), arousal (2.5/6), orgasm (2.72/6), lubrication (3.04/6), and desire (3.18/6).Conclusion: The proportion of patients after total hysterectomy due to cancer has a high rate of psychological and physiological changes, and more counseling and guidance on remedial measures are needed to improve the quality of life.
Keywords: Psychology; surgery; cervical cancer